Research progress of peer education for stroke patients (同伴教育模式在脑卒中患者中的应用研究进展) - WU Yuanxia (吴远霞); WEI Yan (魏艳) (Association of Integrative Nursing, 2024)
With the increasingly serious problem of China's aging society, the number of people suffering from stroke is increasing every year. Most stroke patients are accompanied by various sequelae and complications, which seriously affect the rehabilitation process of patients, increase the possibility of stroke recurrence, and are directly related to stroke mortality. Peer education is an economical, flexible and convenient new education model, which has been widely used in different fields at home and abroad. This review summarizes the domestic and foreign research progress on the application of peer education to stroke patients, in order to provide reference for clinical intervention of stroke patients. (脑卒中是全球第二大死亡疾病, 其发病率呈总体上升且逐渐年轻化的趋势。脑卒中患者大多伴有各种后遗症和并发症, 严重影响患者康复进程, 增加脑卒中复发的风险, 且与脑卒中死亡率直接相关。同伴教育模式是一种经济、灵活、便利的新型教育模式, 在国内外被广泛应用到了不同领域之中。本文对同伴教育应用于脑卒中患者的国内外研究进展进行概述, 以期为脑卒中患者的临床干预提供参考。)